Extent of Insecticide Residue Load in Vegetables Grown under Conventional Farming in Bangladesh - Ahmed, M S; Begum, Afroza; Rahman, M A; Akon, M W; Chowdhury, M A Z (The Agriculturists, 2017)
The study was carried out to detect and quantify the left over residues of eight commonly used insecticides (fenvalerate, diazinon, quinalphos, fenitrothion, acephate, chlorpyriphos, cypermethrin and malathion) in brinjal, yard long bean, bitter gourd, snake gourd, pointed gourd, okra, tomato, hyacinth bean and cabbage samples collected from local market of eight different regions like Jessore, Comilla, Narsingdi, Tangail, Rangpur, Jamalpur, Gazipur and Dhaka during 2011-2012 seasons. Among the170 analyzed samples, 21.78% were contaminated with four insecticides (chlorpyriphos, quinalphos, acephate and cypermethrin) either single or multiple product residue, in which 18.26% samples had residue above MRL. The vegetables of Norsingdi, Jessore and Comilla had more insecticide residue in comparison to other locations. Most of the samples contain chlorpyriphos (13.53%) and quinalphos (8.4%) residue. Acephate, chlorpyriphos and quinaphos were also found as multiple product residues expressing 2.35% of the total samples which were above MRL and 19.41% sample contained single product residue with chlorpyriphos, quinaphos and cypermethrin where 15.88% were of above MRL. Cypermethrin residue was detected only in two samples (brinjal and yard long bean) which were below MRL. The Agriculturists 2016; 14(2) 38-47